2018
DOI: 10.1016/j.amepre.2018.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Health System Affiliation and 30-Day Readmission After Heart Attack in Black Men

Abstract: Introduction Black patients who experience acute myocardial infarction and receive care in high minority-serving hospitals have higher readmission rates. This study explores how hospital system affiliation (centralized versus decentralized/independent) impacts 30-day readmissions after acute myocardial infarction in black men. Methods In 2018, the Healthcare Cost and Utilization Project State Inpatient Database (2009– 2013) was used to observe 30-day readmission for acute myocardial infarction by race, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Numerous studies have shown that the centralization of low-volume surgical procedures, oncologic surgery and trauma patients lowers mortality [32][33][34]. However, this is not true in every diagnosis and patient group [35]. Therefore, we must delve into which diagnoses and patients benefit from centralization, which is the next step in our research.…”
Section: Mortality By Specialty and Centralization Of Servicesmentioning
confidence: 99%
“…Numerous studies have shown that the centralization of low-volume surgical procedures, oncologic surgery and trauma patients lowers mortality [32][33][34]. However, this is not true in every diagnosis and patient group [35]. Therefore, we must delve into which diagnoses and patients benefit from centralization, which is the next step in our research.…”
Section: Mortality By Specialty and Centralization Of Servicesmentioning
confidence: 99%